SUCCESSFUL PERFORMANCE APPRAISAL IN A SCHOOL ORGANISATION - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
The present paper discusses the importance of performance appraisal using the school as the siteof implementation. Schools, just like any other public or private organization, have manyemployees or staff members whose performance has to be periodically appraised for theirindividual growth and that of their organisation. The paper argues that performance appraisalshould be viewed as a process, and not simply as the creation of ubiquitous standards. Theoverriding purpose of performance appraisal is to help staff to improve and, thus, to improveorganisational effectiveness. Performance appraisal therefore addresses institutional needs aswell as staff member needs, abilities, motivation and expectancies. Effective appraisal systemsmust possess the attributes of clarity, openness, and fairness. Appraisal activities, as an ongoingprocess should connect the process to organisational functioning and have as their focus staffimprovement, not simply salary adjustment and or disciplinary action. Appraisal systems arerelated to institutional productivity requirements. They are expected to reveal under- productiveunits and to serve as a response to focus attention on problem areas and also reward productiveunits and staff.